Effects of red and infrared laser on post extraction socket repair in rats subjected to alendronate therapy - Gonçalves, Fernanda Castanheira [UNESP]; Mascaro, Bruno Arruda [UNESP]; Oliveira, Guilherme José Pimentel Lopes de; Spolidório, Luis Carlos [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (FapUNIFESP (SciELO), 2023)
This study evaluated the effect of photobiomodulation therapy (PBMT) with a red or infrared laser on the repair of post extraction sockets in rats administered alendronate (ALN). Forty male rats were randomly allocated into four groups: Control Group (CTR): subcutaneous administration of saline solution throughout the experimental period; Alendronate Group (ALN): subcutaneous administration of alendronate during the entire experimental period; Alendronate/Red Laser Group (ALN/RL): administration of ALN and irradiation with a GaAlAs laser (λ 660 nm); and Alendronate/Infrared Laser Group (ALN/IRL): administration of ALN and irradiation with a GaAlAs laser (λ 830 nm). The first lower molars were extracted 60 days after the beginning of the administration of the drugs. The PBMT was applied after tooth extraction (7 sessions with intervals of 48 hours between sessions). Thirty days after tooth extraction, the animals were euthanized. Micro-CT and histometric analysis were performed to assess the bone healing and soft tissue repair of the tooth socket. The ALN group presented with more bone than the CTR; however, most of this bone was necrotic. ALN does not affect the bone microarchitecture. On the other hand, PBMT with IRL enhances the bone density due to the increase in the number and reduction in the spacing of the trabeculae. The amount of vital bone and connective tissue matrix was higher in the ALN/RL and ALN/IRL groups than in the ALN and CTR groups. PBMT enhanced the healing of the post extraction sockets in rats subjected to ALN administration. Furthermore, IRL improved the new bone microarchitecture.